Application of programmed trajectory motion control for the grids containing distributed generation; Innovative Smart Grid Technologies - Asia (ISGT-Asia) - Prokhorov A. V. Anton Viktorovich; Беляев Н. А. Николай Александрович; Khrushchev Yu. V. Yuri Vasilievich; Vasilev A. S. Alexey Sergeevich; Li Wang (2016, 2016)
Title screen